Neva Leona Boyd : a social worker at the origin of popular and theatrical education (1876 - 1963) (Olhares, 2025)
Português (Brasil) - Detectado swap_horiz Inglês Texto de origem    clear           1.048 / 5.000Resultados de traduçãoResultado da traduçãoWho is Neva Leona Boyd (1876 - 1963)? What is the significance of her contribution to Social Work in contemporary times? This article aims to announce a social worker, intellectual and social activist to Brazilian social workers, who was among the 20 pioneers of the state of Illinois (USA) in the city of Chicago in the late 19th century and early decades of the 20th century. During the course of the research, in dialogue with great names in Brazilian Social Work, it was noted that we were completely unaware of the life and work of this thinker who is one of the greatest references not only in Social Work, but also in theatrical games and theatrical pedagogy, having arrived in Brazil through the area of ​​Performing Arts. The work revisits the experience of Hull House, from the birth of Social Work in the state of Illinois to the contributions to contemporary Social Work, considering Theater and Education as potential areas of dialogue from the perspective of popular education and the professional ethical-political project of Social Work.
Keywords: Theater; Education; Neva Leona Boyd